Coronavirus disease 2019—The principles of the curve, explained simply. Issue 7 (1st June 2020) - Jozaghi, Yelda
Abstract: In the setting of the coronavirus disease 2019 pandemic, the concept of the disease curve has become ubiquitous in medicine and across society. Nevertheless, even among medical specialists, there are common misconception about the curve and how it affects population outcomes. This article provides a simple review of the various population dynamics at play. Principles such as the area under the curve and the threshold of capacity are discussed and simply conceptualized. Understanding the fundamental characteristics of a problem can allow us to see it with more clarity. By the end of the article, the reader will gain an effortless a sense of insight on this topic.